La « réussite » en éducation : dispositif et mode de gouvernement contemporain - Mariagrazia Cairo Crocco (Recherches en Éducation)
“Success” seems to have been one of the watchwords of education, training and guidance policies in recent decades. Succeeding in order not to fail, increasing one's skills and "human capital". Success" is a political concern that also relates to experimentation and creation of knowledge and to singular ways of living. On the one hand, constantly renewed measures are experimented with, rejected and then recycled in new forms ; on the other hand, processes of subjectivation and subjugation intersect in constantly changing workspaces. Success seems to be an individual effort but also a social, economic and political obligation. Michel Foucault's analyses of power and governmentality can provide a relevant reading grid to grasp 'success' as a 'device' embedded in contemporary political rationality.